2020
DOI: 10.1111/and.13549
|View full text |Cite
|
Sign up to set email alerts
|

Association of lifestyle factors with semen quality: A pilot study conducted in men from the Portuguese Trás‐os‐Montes and Alto Douro region followed in fertility support consultations

Abstract: A cross‐sectional pilot study was conducted in men followed in fertility consultations, from the portuguese Trás‐os‐Montes and Alto Douro region, in order to associate several lifestyle factors with the spermatic parameters. Of a total of 522 men, 373 were compared based on the occupational exposure to harmful factors, smoking habits and practice of physical exercise per week, and the other 149 men according to their body mass index (normal weight vs. overweight vs. obesity). In the absence of harmful occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…In our opinion, the challenge lies in separately studying potential confounders for these findings. Previous studies have reported the association between worsening semen parameters and factors such as diet [ 2 ], caffeine consumption [ 3 ], sedentarism [ 4 ], occupational exposure [ 5 ], use of medications and other drugs, cannabis [ 6 ], and exogenous testosterone [ 7 ]. The authors conducted a linear regression model to adjust for confounding factors (BMI, alcohol consumption, smoking, and others), and the findings were consistent.…”
Section: Commentmentioning
confidence: 99%
“…In our opinion, the challenge lies in separately studying potential confounders for these findings. Previous studies have reported the association between worsening semen parameters and factors such as diet [ 2 ], caffeine consumption [ 3 ], sedentarism [ 4 ], occupational exposure [ 5 ], use of medications and other drugs, cannabis [ 6 ], and exogenous testosterone [ 7 ]. The authors conducted a linear regression model to adjust for confounding factors (BMI, alcohol consumption, smoking, and others), and the findings were consistent.…”
Section: Commentmentioning
confidence: 99%
“…Obese men are more likely to have decreased sperm concentration, and to have sperm with abnormal morphology, damaged chromatin, and reduced motility [ 5 , 6 ]. BMI is closely and negatively correlated with sperm quality parameters, and obese men are three times as likely to have abnormal sperm parameters as normal men [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Üreme çağındaki çiftlerin en sık karşılaştığı ve yaklaşık %10-15'ini etkileyen bir sağlık sorunudur. Fertiliteyi olumsuz etkileyen faktörler kadın veya erkeğe ait anatomik ve fizyolojik faktörler olabileceği gibi (1), bunların yanı sıra son yıllarda değişen yaşam tarzı koşullarının da fertiliteyi olumsuz etkileyebileceği belirtilmektedir (2)(3)(4)(5). Günümüzde bireysel ve toplumsal yaşanan sorunlardan dolayı stres birçok bireyin yaşamını etkilemektedir.…”
Section: Introductionunclassified